Learning Module Based on Verses About the Water Cycle in the Quran for Elementary School Students - Asmaul Husna; Muhaemin Muhaemin (Pedagogik Journal of Islamic Elementary School, 2022)
This study focuses on creating verse-based learning modules on the water cycle as mentioned in the Quran. The objectives include assessing the prototype of this module among fifth-grade students at SDN 50 Bulu Datu and evaluating its validity. Following the Research and Development approach, the study employs the ADDIE development model with analysis, design, and development stages. It was carried out at SDN 50 Bulu Datu in Palopo City, with 30 fifth-grade students as participants. Data collection methods encompassed observation, documentation, interviews, and validation processes. The findings indicate that the Water Cycle learning module, based on Qur'anic verses, underwent validation by three validators, incorporating revisions based on their feedback. The validity assessment revealed that the language aspect achieved 80% validity, while material validity reached 86%, signifying a high level of validity. Moreover, the design of the module attained a 90% validity rating, indicating strong validity in this area.